Intriguing Interpretation of Dyads in Common-Practice Tonal Music - Yosef Goldenberg (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2021)
The study offers a systematic exploration of situations in which dyads in common-practice tonal music change their meaning, when repeated or as pivots. The most common such situation is thirds that serve as either the upper or the lower pair of consonant triad members, most often with the tonic as one of the options. Sometimes, however, an implied harmony turns out to be dissonant. Occasionally, dyads other than thirds are also subject to reinterpretation. In exceptional circumstances, dyads do not imply complete harmonies.
Keywords: dyads; pivot chords; reinterpretation; harmony; common-practice tonal music